Integer Norm for Difference Assessment of the Frame Elements Considering the White Balance - Ivashchenko, M.V.; Okhrymchuk, D.D.; Lyushenko, L.A. (Управляющие системы и машины, 2019)
The proposed concept suggests a method, based on which a synthesis of an integer norm can be performed, which takes into account the white balance of the camera when performing the evaluation of the difference between the elements of an image. This idea is based on modifying the internal calculations of the camera, aimed at assessing the colour of the image element, using the process of colour model reduction that is embedded inside the camera, to the colour model of the classical representation. The use of this approach provides a number of advantages within the framework of systems in which there is a solution of computer vision problems in terms of using both graphical processing and artificial intelligence.